Strategy for managing mangrove forest ecosystems in Tuapejat Bay, Mentawai Islands Regency, West Sumatra - Zaryaningsih, Atika; Kamal, Eni; Damanhuri, Harfiandri (Acta Aquatica: Aquatic Sciences Journal, 2022)
This study aimed to analyze the management of the mangrove forest ecosystem in Tua pejat bay, Mentawai Islands district, West Sumatra. This research has been carried out for three months starting from September to November 2021 which is located in the Mangrove forest area of Tua Pejat bay, Mentawai archipelago district, West Sumatra. The object of this research is the community around the Mangrove forest area. This research used survey method. SWOT analysis is used to determine the strategy in determining direction and knowing the implications of appropriate policies for the management of mangrove forest areas in Tua Pejat bay, Mentawai archipelago, West Sumatra. Respondents were determined by purposive sampling as many as 98 respondents. Based on the results of the study, opportunities and threats in the management of the mangrove forest ecosystem in Tuapejat Bay, a strategy is needed to achieve sustainable utilization of the existing potential and its management must be carried out seriously by managing the mangrove forests in Tuapejat Bay by helping improve the community's economy. Tuapejat village such as in the field of fisheries and tourism.Keywords: mangrove forest ecosystem; Tua Pejat; management